2022
DOI: 10.3389/fphar.2022.980918
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical safety evaluation of Macleaya Cordata extract: A re-assessment of general toxicity and genotoxicity properties in rodents

Abstract: Macleaya cordata extract (MCE) is widely used for its diverse pharmacological actions and beneficial effects on farm animals. Modern pharmacological studies have shown that it has anti-inflammatory, anti-cancer, and anti-bacterial activities, and is gradually becoming a long-term additive veterinary drug used to improve animal intestinal health and growth performance. Although some evidence points to the DNA mutagenic potential of sanguinarine (SAN), a major component of MCE, there is a lack of sufficient basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Br., which is a natural, pollution-free green product. The MCE standardized extraction process is referenced by Dong (2022) [ 13 ]. In a previous study, five species of MCE components were identified, including Benzophenanthridine, Benzyltetrahydroisoquinoline, Protopine, Protoberberine, and Tetrahydroptotoberberine, and the specific components refer to Dong (2021) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Br., which is a natural, pollution-free green product. The MCE standardized extraction process is referenced by Dong (2022) [ 13 ]. In a previous study, five species of MCE components were identified, including Benzophenanthridine, Benzyltetrahydroisoquinoline, Protopine, Protoberberine, and Tetrahydroptotoberberine, and the specific components refer to Dong (2021) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note, however, that further research is necessary to fully understand the safety and efficacy of halicin in different animal models and ultimately in human subjects. Nonetheless, these results provide insight into the potential of halicin as a therapeutic agent ( Dong et al, 2022a ).…”
Section: Resultsmentioning
confidence: 98%
“…Antimicrobial drugs including ofloxacin, amikacin, macleaya cordata extract, and nitazoxanide are also classified under GHS Category 5 (>2000 mg/kg b.w. ), 5, 5, 4, and 4, respectively [ 54 , 55 , 56 , 57 ]. Post-mortem examination of both deceased and surviving mice in all dose groups revealed no abnormalities in organs in both intraperitoneal and oral administration acute toxicity tests.…”
Section: Resultsmentioning
confidence: 99%